Visualizing curvilinear cylindrical engineering members in 3-D environment with motion path - Sidhu M.S. (2023)
Visualizing and understanding engineering concepts from non-dynamic media has been difficult in the past. In this paper, two models of 3-D curvilinear cylindrical engineering members that could be visualized better in a virtual environment are discussed. These 3-D models can be used to analyze common visualization engineering problems with better understanding as opposed to the conventional method. More significantly it helps users (students) visualize and solves engineering problems in time and space by guiding and showing the correct steps in a well-structured manner. The paper further discusses the preliminary design and outcomes of an evaluation of the 3-D curvilinear cylindrical engineering members. 2009 IEEE.